'Stood to rest': reorientating necrogeographies for the 21st century. (2nd January 2023) - Gould, Hannah; Arnold, Michael; Dupleix, Tony; Kohn, Tamara
ABSTRACT: Human bodies are typically buried underground, horizontally 'in repose'. To the extent that this orientation has become the standard; it is a non-choice that is under-interrogated by scholars. In this paper, we discuss innovations which allow for the vertical orientation of the body within the earth and for the vertical stacking of remains above the earth in high-rise structures. Both of these boundary-pushing forms of disposition address imminent shortages in the land allocated for cemeteries in the context of intense urbanisation and a peaking death rate. They also promise to transform the necrogeography of contemporary cities and intimate relations between the living and the dead. This paper is a collaboration between the DeathTech Research Team and the Managing Director of Upright Burials, where the dead are 'stood to rest' in shaft graves. The pragmatic advantages of vertical burial are easily explicated, but in this paper, we focus on the cultural and symbolic dimensions of this largely unfamiliar spatial relation and the challenges of 'reorienting' the public towards this new form of disposition.